Noncommutative mathematics for quantum systems / Uwe Franz, Adam Skalski. - Franz, Uwe; Skalski, Adam, 1978- (Cambridge University Press, 2016)
"Discusses two current areas of noncommutative mathematics, quantum probability and quantum dynamical systems"-- Provided by publisher
Keywords: Probabilities.; Quantum theory.; Potential theory (Mathematics)